Al-Quran Memorization Learning Using the Edutainment Method at Al-Kiswah IT Kindergarten, Bengkulu City - Tryce Ayu Lestari S; Aziza Aryati; Hengki Satrisno (Amorti: Jurnal Studi Islam Interdisipliner, 2025)
This study aims to analyze the implementation of the edutainment method in Al-Qur'an memorization learning at Al-Kiswah IT Kindergarten, Bengkulu City, and to examine its contribution to improving children's memorization abilities and learning experiences. The study employed a qualitative case study approach to obtain an in-depth understanding of learning practices within a natural educational setting. Data were collected through classroom observations, in-depth interviews with school principals, teachers, and parents, as well as document analysis related to learning plans and students' memorization progress. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing. The findings indicate that the edutainment method creates an engaging, interactive, and child-centered learning environment by integrating educational games, storytelling, songs, rhythmic repetition, movement, audiovisual media, and collaborative learning activities into the memorization process. These instructional strategies enhance children's motivation, concentration, self-confidence, and active participation while facilitating better memorization and long-term retention of Qur'anic verses. Furthermore, the method contributes to the development of positive character traits, including discipline, cooperation, responsibility, and a stronger emotional attachment to the Qur'an. The study concludes that the edutainment method is an effective pedagogical approach for supporting Al-Qur'an memorization among early childhood learners because it accommodates children's developmental characteristics while promoting meaningful and enjoyable learning experiences. The findings provide practical implications for teachers, parents, and Islamic educational institutions in developing innovative and child-friendly Qur'anic memorization programs.